Identification of the effective water availability from streamflows in the Zerafshan river basin, Central Asia - Olsson, O.; Gassmann, M.; Wegerich, Kai; Bauer, M. (Elsevier, 2010)
Quantitative estimates of the hydrologic effects of climate change are essential for understanding and solving potential transboundary water conflicts in the Zerafshan river basin, Central Asia. This paper introduces an identification of runoff generation processes and a detection of changes in hydrological regimes supporting Mann-Kendall trend analysis for streamflows. By this, the effective available and future water resources are identified for the Zerafshan. The results for the subbasins in the upper Zerafshan and for the reference station at the upper catchment outlet indicate that glacier melt is the most significant component of river runoff. The Mann-Kendall trend analysis confirms the regime analysis with the shift in the seasonality of the discharge. Furthermore, the results of the Kendall-Theil Robust Line for predicted long-term discharge trends show a decreasing annual discharge. The experience gained during this study emphasizes the fact that the summer flood, urgently required for the large irrigation projects downstream in Uzbekistan, is reduced and more water will be available in spring. Additionally, following the estimation of future discharges in 50 and 100 years the hydrological changes are affecting the seasonal water availability for irrigation. This analysis highlighted that water availability is decreasing and the timing of availability is changing. Hence, there will be more competition between upstream Tajikistan and downstream Uzbekistan. Planned projects within the basin might have to be reconsidered and the changed scenario of water availability needs to be properly taken into account for long-term basin scale water management.